Penerapan Massage Plexus Sacralis Terhadap Masalah Keperawatan Nyeri Akut pada Pasien Post Sectio Caesarea - Firda Vinanda; Rinda Intan Sari; Anis Ardiyanti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The Caesarean Section (C-Section) procedure is one of the most common surgical methods for childbirth, performed through an incision in the abdominal wall (laparotomy) and the uterine wall (hysterotomy). Despite its effectiveness in ensuring maternal and fetal safety, one of the major postoperative complaints reported by patients is pain. Pain itself is defined as an unpleasant sensory and emotional experience associated with actual or potential tissue damage, which is subjective and can only be described by the person experiencing it. Unmanaged pain may negatively affect postoperative recovery, emotional well-being, mobility, and breastfeeding initiation. Therefore, appropriate nursing care interventions are essential to help patients achieve comfort and recovery. This scientific paper explores the implementation of sacral plexus therapy as part of nursing interventions to address pain problems in post-C-section patients. The study employed a case study approach that applied the nursing care process, which includes comprehensive assessment, formulation of nursing diagnoses, planning, implementation of interventions, and evaluation. Nursing care was carried out over a period of 72 hours (3x24 hours), with pain intensity and patient comfort levels monitored throughout the process. The evaluation results showed that all nursing diagnoses related to pain were successfully resolved within the given timeframe. Specifically, the application of sacral plexus therapy proved effective in reducing the intensity of postoperative pain and improving overall comfort, enabling patients to gradually regain mobility and adapt to their postpartum condition. In conclusion, sacral plexus therapy can serve as a complementary and non-pharmacological intervention within nursing care to effectively manage pain in post-C-section patients. These findings highlight the importance of innovative and holistic approaches in nursing practice to improve patient recovery and quality of care after surgical childbirth.